(3GdbGfhf GdOhdj GdNGUs - (3GdaJdGhj(B, (3Sgjd MSjfs ((3GdbGgQIs (3GdecJH GdeUQj dJhRjY GdeWHhYGJs, 2002)
(3HGdfX``````Q Edj Cf GdbGfhf GdOhdj GdNGU jfXe ehVhYGJ bGfhfjI eJYOOI , hgj GdLfSjI hGdehWf hGdeQcR GdbGfhfj ddCLGfH hJfGRY GdGNJUGU GdbVGFj h JfGRY GdbhGfjf , abO GNJda GdabgGA aj hVY JYQja LGeY eGfY ddbGfhf GdOhdj GdNGUJfGhd gPG GdcJGH GdaUd CdChd (B: (3GdeHGOiA GdYGeI ddbGfhf GdOhdj GdNGU GdaUd GdKGfj (B: (3GdLfSjI GdaUd GdKGdK (B: (3Gde````````hGWf GdaUd GdQGHY (B: (3eQcR GdCLGfH GdaUd NGeS (B: (3JfGRY GdbhGfjf GdaUd GdSGOS (B: (3GdGNJGU GdbVGA GdOhdj GdaUd GdSGHY (B: (3JfajP GdCMcGe h GdbQGQGJ GdCLfHjIs
Keywords: (3GdLfSjIs; (3bGfhf GdOhdj GdNGUs